PENGARUH PENGGUNAAN SISTEM INFORMASI AKUNTANSI TERHADAP PENINGKATAN PENDAPATAN USAHA COFFE SHOP DI KOTA MATARAM - Paozan; Triana Lidona Aprilani; Muhammad Habibullah Aminy; Fathurrahman, Fathurrahman (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to analyze the influence of accounting information system (AIS) usage on the increase of business income in coffee shops in Mataram City. The background of this research is the rapid growth of coffee shops in line with the increasing coffee consumption among society, while many business owners still lack a structured financial management system. This research uses a quantitative method with a survey approach. The sample includes 30 coffee shops that have implemented an accounting information system, selected through purposive sampling. The data were analyzed using validity and reliability tests, simple linear regression, and t- tests. The results show that the use of an accounting information system significantly affects the increase in business income of coffee shops in Mataram City. This is supported by a significance value of < 0.05 and a t-count value higher than the t- table. These findings indicate that accounting information systems help business owners in more accurate financial recording, effective decision-making, and better financial planning.